Expanding LGBTI rights in Colombia during Internal Armed Conflict and Emergent Transitional Justice (2006-2016): Process Tracing Tactics of Influence and Levels of Effectiveness of National Non-Governmental Organizations Specialized in LGBTI Rights - Paredes Minango, Carlos Andrés (2023)
This interdisciplinary research analyses the expansion of LGBTI2 rights in Colombia in a context of internal armed conflict and emergent transitional justice process from 2006 to 2016. Through a logic of retroduction, my original contribution to knowledge is finding that national non-governmental organizations (NGOs), specialized in LGBTI rights, deployed a multiplicity of tactics of influence to advance their goals. Through process tracing and document analysis, this thesis recognizes the suitability of the middle range theory of transnational advocacy networks, to comprehend tactics of influence and levels of effectiveness of national LGBTI rights NGOs, as well as to locate them as significant actors in expanding LGBTI rights in Colombia.